Neuropathological Characterisation of McLeod Syndrome With a Proposed New Grading System - Reuss, Anna Maria; Renerts, Klavs; Hortobágyi, Tibor; Geser, Felix; Haybaeck, Johannes; Danek, Adrian; Fuhr, Peter; Udd, Bjarne; Zeman, Adam; Ross, Reichard R.; Rushing, Elisabeth J.; Jung, Hans H. (Neuropathology and applied neurobiology, 2025)
ABSTRACT Aims X‐linked McLeod neuroacanthocytosis syndrome (MLS) is a rare neurodegenerative disorder characterised by the presence of red blood cell acanthocytosis and a chorea syndrome. Analogous to Huntington's disease (HD), MLS displays cognitive and behavioural symptoms besides the progressive movement disorder. This study aimed to describe the neuropathology of MLS in the largest case series to date. Methods Clinical data were collected, and neuropathological assessments were performed on eight male MLS patients originating from Finland, New Zealand, Switzerland, Scotland and the United States. Results Macroscopic data were available from six patients, with five showing atrophy of the basal ganglia, which was more pronounced in the caudate nucleus and to a lesser extent in the putamen and pallidum. Histology revealed neuronal loss and accompanying gliosis in the basal ganglia of all patients. The extent of these alterations varied widely, with a decreasing gradient of severity from the caudate nucleus to the putamen and the pallidum, mirroring the macroscopic findings. In addition, we detected intraneuronal vacuoles in the striatum in half of the patients. Conclusions MLS neuropathology is characterised macroscopically by atrophy and microscopically by neuronal loss and gliosis of the basal ganglia, with a decreasing gradient of severity from the caudate nucleus, the putamen to the pallidum. Analogous to the grading system for HD, we propose a neuropathological grading system for MLS based on the current observations in the largest MLS cohort examined to date. Standardised criteria are crucial for neuropathological assessment of this extremely rare disease. Summary The neuropathology of McLeod syndrome is characterised by neuronal loss, gliosis and atrophy of the basal ganglia. There is a severity gradient from the caudate nucleus to the putamen and pallidum, in decreasing order. Intraneuronal vacuoles in the basal ganglia of McLeod syndrome patients are a microstructural hallmark of advanced disease. Comprehensive investigation of the largest McLeod syndrome patient cohort to date allows for the proposal of a standardised grading system for the neuropathological assessment of McLeod syndrome. We report the neuropathological findings of the X‐linked McLeod neuroacanthocytosis syndrome (MLS), a very rare neurodegenerative disorder characterised by red blood cell acanthocytosis, chorea syndrome similar to Huntington’s disease, and additional neuromuscular and cardiological involvement. There was varying atrophy of basal ganglia, pronounced in the caudate nucleus. Histologically, we found neuronal loss and accompanying gliosis with additional striatal intraneuronal vacuoles in four of eight patients. Analogous to the HD grading system, we propose a neuropathological grading system for MLS.